An ultra-wideband orthogonal-beam directional graphene-based antenna for THz wireless systems - Sasmita Dash; Constantinos Psomas; Amalendu Patnaik; Ioannis Krikidis (Scientific Reports, 2022)
Abstract In terahertz (THz) wireless systems, graphene shows a tremendous promise for the implementation of miniaturized and reconfigurable antennas due to its unique tunable property. This paper presents a wideband beam reconfigurable directional antenna for THz wireless communication systems. The antenna design concept is based on the Yagi-Uda antenna working principle. The proposed antenna consists of a centre-fed graphene-based driven dipole and three graphene-based parasitic elements on either side of the driven element. These graphene-based parasitic elements either act as directors or reflectors by controlling the surface conductivity of these elements. The surface conductivity of the elements is adjusted individually by applying a bias voltage via the chemical potential of the graphene. The main beam direction of the antenna can be reconfigured by controlling the chemical potentials of the graphene-based parasitic elements. Specifically, the proposed graphene THz antenna reconfigures the main beam into four orthogonal directions (0°, 90°, 180° and 270°) at an operational frequency 1.25 THz. The antenna achieves a directional symmetrical radiation pattern with 14 dBi gain and a front-to-back ratio of 15.5 dB. Furthermore, the proposed graphene THz antenna provides a stable reflection coefficient in four reconfigurable cases and an ultra-wideband of 10-dB impedance bandwidth of 120%. Therefore, this novel design technique of graphene-based ultra-wideband high gain beam reconfigurable THz antenna is promising for THz wireless systems.